Morbidity patterns among the welders of eastern Nepal: a cross-sectional study. Issue 1 (December 2016) - Budhathoki, Shyam; Singh, Suman; Niraula, Surya; Pokharel, Paras
Abstract Background Welding process has many hazards that the welders are exposed to resulting in numbers of health effects and diseases. Safety measures and practices among welders are important ways of preventing or reducing the health hazards associated with this occupation. We conducted this study to find out the morbidity patterns among the welders working in eastern Nepal. Methods A cross sectional study was conducted among 300 welders using semi structured questionnaire. Morbidity categories were classified based on symptoms experienced in past 6 months. Results All the welders learned welding by apprenticeship, without any formal health and safety training. Injury was the most common problem at work followed by skin problems and eye symptoms. Age of the welders, duration of employment & welding hours per day were associated with the morbidities among the welders. Conclusions There is a need for occupational health services for welders in Nepal. While further research may be required to make policy recommendations, the current study provides a baseline morbidity burden among these welders to look for interventions to promote health and safety at work for this neglected group of workers in Nepal.